World food prospects: critical issues for the early twenty-first century - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul; Rosegrant, Mark W. (International Food Policy Research Institute, 1999)
This report discusses six issues that could influence the world food situation in the twenty-first century: the relationship between policy related variables and the nutritional status of children, the relationship between current market trends for wheat, maize and rice and their potential impact on producer income, food production, and food stocks; the role of developing countries in the next round of World Trade Organization negotiations; and three topics related to increasing productivity on small-scale farms: the potential of agroecological approaches, the role of biotechnology, and the relevance of new information technology and precision farming.